(untitled) (Journal of Shaheed Suhrawardy Medical College, 2020)
Context: Irritable bowel syndrome (IBS) is one of the most common chronic gastrointestinal (GI) disorders. Recently, many studies have found the association between irritable bowel syndrome (IBS) & the psychological factors. Aims: The study aimed to determine the relationship between psychological features and different subtypes and severity of irritable bowel syndrome. Settings and Design: This cross-sectional study was performed among 208 outpatients diagnosed as irritable bowel syndrome in two government medical college hospitals of Dhaka city from January, 2015 to December, 2015. The subtypes and severity of irritable bowel syndrome were assessed by Rome-III and ‘Irritable bowel syndrome severity scoring scale’ respectively. Psychological features were assessed by Brief Symptom Inventory consisting 53 items of psychological problems. Results: Global severity index of Brief Symptom Inventory, which is the best indicator of psychological distress, was found significantly higher in respondents with diarrhea predominant IBS (p< 0.001) and severe IBS patients (p< 0.001). Mean scores of other psychological problems among Brief Symptom Inventory -53 subscales (hostility, interpersonal sensitivity, paranoid ideation, psychoticism, depression, anxiety) were significantly higher in diarrhoea predominant IBS and severe IBS patients compared to the others (p<0.001). Severity score of irritable bowel syndrome was also moderately correlated with Global severity index (r= 0.417, p<0.001). Conclusions: This study found relationship between psychological features and different pattern of irritable bowel syndrome. Hence, the appropriate psychological assessment and counseling in IBS patients is critically important. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 110-114